Strengthening Management of BUMDes to Increase Income and Welfare of Hendrosari Village, Menganti District, Gresik Regency - Aries Kurniawan; Beni Dwi Komara; Muhammad Ghufran Ramdhani; Ragillia Ragillia (OJS Universitas Muhammadiyah Gresik, 2020)
In the PKM program, our partner is the Potential Development of Hendrosari Village, Menganti District, Gresik Regency. The location of this village is close to Benowo District, Surabaya City, East Java Province. This village has the potential to strengthen management in the management of Tourism Villages and the results of products managed by the Village Owned Enterprises. This tourism village is located on village land with an area of around 10 hectares with the potential for nature tourism with the concept of education.Based on the results of interviews and observations there are two problems faced by partners, 1) The lack of optimal management of Village-Owned Enterprises (BUMDEs) that manage Eduwisata. 2) Lack of knowledge and community participation to develop the potential of the village and Lontar Sewu tourism. Some of the things planned by the PKM team are to streghten management BUMDes by holding seminars and workshops to improve the knowledge and abilities of the Hendrosari Village community in general and the BUMDes management in particular. The purpose of this activity is to improve capabilities that have an impact on good business management and increase of capabilities BUMDes management, community and village income.This activity was realized with an approach in the form of making a sustainable cooperation program until the end of PKM, creating a family atmosphere between the two and understanding that the problems experienced were a shared problem so that they could be solved together according to the level of responsibility to achieve the expected benefits, namely increased yields, production and productivity and competitiveness, independence and welfare of the community.